Migratory and Dancing Macrophage Subsets in Atherosclerotic Lesions - McArdle, Sara (Circ Res, 2019)
RATIONALE: Macrophages are essential regulators of atherosclerosis. They secrete cytokines, process lipoproteins and cholesterol, and take up apoptotic cells. Multiple subsets of plaque macrophages exist and their differential roles are emerging. OBJECTIVE: Here, we explore macrophage heterogeneity in atherosclerosis plaques using transgenic fluorescent mice in which subsets of macrophages are labeled by GFP, YFP, neither or both. The objective was to define migration patterns of the visible subsets and relate them to their phenotypes and transcriptomes. METHODS AND RESULTS: Apoe(−/−) Cx3cr1(GFP) Cd11c(YFP) mice have 4 labeled groups of macrophages in their aortas. The visible subsets show varying movement characteristics. GFP and GFP+YFP+ macrophages extend and retract dendritic processes, dancing on the spot with little net movement while YFP macrophages have a more rounded shape and migrate along the arteries. RNA sequencing of sorted cells revealed significant differences in the gene expression patterns of the 4 subsets defined by GFP and YFP expression, especially concerning chemokine and cytokine expression, matrix remodeling, and cell shape dynamics. Gene set enrichment analysis showed that GFP+ cells have similar transcriptomes to cells found in arteries with tertiary lymphoid organs and regressing plaques while YFP+ cells were associated progressing and stable plaques. CONCLUSIONS: The combination of quantitative intravital imaging with deep transcriptomes identified four subsets of vascular macrophages in atherosclerosis that have unique transcriptomic profiles. Our data are the first to link vascular macrophage transcriptomes to their in vivo migratory function. Future work on the functional significance of the change in gene expression and motility characteristics will be needed to fully understand how these subsets contribute to disease progression.